2013
DOI: 10.2478/bvip-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

First Isolation of the H1N2 Swine Influenza Virus in Polish Pig Farm

Abstract: The paper describes an outbreak of swine influenza, which was the first H1N2 outbreak confirmed in pig farm in Poland. The outbreak occurred in October 2011 in the farrows to finish farm, first in the fattening units, and subsequently in the reproduction and weaning sectors. Samples of the lungs taken from dead gilts were tested by the use of real time and multiplex PCR, sequencing, and virus isolation methods. The amplification of the genetic material extracted from the lungs confirmed the presence of the M1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(53 reference statements)
0
3
0
1
Order By: Relevance
“…Respiratory diseases in pigs are often considered as multifactorial problems caused by various pathogens (viral and bacterial) in combination. The most common infectious agent responsible for respiratory infection in pigs are: swine influenza virus (SIV), porcine reproductive and respiratory syndrome virus (PRRSV), Pasteurella multocida (Pm), Actinobacillus pleuropneumoniae, Mycoplasma hyopneumoniae [6,7]. These pathogens may act together to increase the severity and duration of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory diseases in pigs are often considered as multifactorial problems caused by various pathogens (viral and bacterial) in combination. The most common infectious agent responsible for respiratory infection in pigs are: swine influenza virus (SIV), porcine reproductive and respiratory syndrome virus (PRRSV), Pasteurella multocida (Pm), Actinobacillus pleuropneumoniae, Mycoplasma hyopneumoniae [6,7]. These pathogens may act together to increase the severity and duration of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity estimates vary greatly but are of little value without consideration of other infectious agents. Morbidity estimates have been reported to increase by 2–100% when exposed to various IAV biotypes, and mortality has been reported to range from 1% to 10% ( Ma et al, 2010 ; Welsh et al, 2010 ; Markowska-Daniel et al, 2013 ). IAV is a common infectious agent providing a significant contribution to PRDC and subsequent mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis revealed that Polish H1N2 is located in the phylogenetic tree in the clade of the human swine lineage marked as a group A (Kowalczyk et al, 2012). The highest nucleotide similarity of the HA1 Polish H1N1 virus with H1N2 strain was observed for A/Swine/Poland/01311/2009 (66.9%) (Markowska-Daniel et al, 2013b). An external gene of Polish H1N2 isolate indicates that it is most similar to a subgroup, which evolved at the beginning of 1990's and formed a new antigenic subcluster with the novel European and the Asian human influenza viruses and SIV isolates H1N2 and H3N2 from around year 2000 (Kowalczyk et al, 2012).…”
Section: Swine Iavmentioning
confidence: 97%